Reduction of Proliferating Olfactory Cells and Low Expression of Extracellular Matrix Genes Are Hallmarks of the Aged Olfactory Mucosa - Ueha, Rumi; Shichino, Shigeyuki; Ueha, Satoshi; Kondo, Kenji; Kikuta, Shu; Nishijima, Hironobu; Matsushima, Kouji; Yamasoba, Tatsuya (Frontiers in Aging Neuroscience, 2018)
Background: The incidence of olfactory impairment increases with age; however, the detailed molecular and cellular mechanisms underlying this increase are yet to be determined. Methods: We examined the influence of aging on olfactory receptor neurons (ORNs), which are maintained by a unique stem cell system, from olfactory progenitor cells to mature ORNs, by histological comparisons of the physiological status of the olfactory epithelium between young adult and aged mice. Furthermore, we clarified the expression of genes encoding inflammatory cytokines, neurotrophins, growth factors, and extracellular matrix proteins to reveal the molecular mechanisms underlying olfactory impairment caused by aging. Results: The numbers of mature and immature ORNs, but not olfactory progenitors, decreased in the aged olfactory epithelium, with a concurrent reduction in Ki-67-positive proliferating cells. Transcriptome analyses revealed an increase in Il6, encoding a component of senescence-associated secretary phenotypes (SASP), and a decrease in Igf1, encoding a growth factor for ORNs, in the aged nasal mucosa. Interestingly, expression levels of several extracellular matrix genes, including Col1a2, decreased in the aged nasal mucosa. Consistent with the transcriptional changes, the number of Col1a2-GFP-positive cells decreased in the aged lamina propria. Conclusions: Our data suggest that reduction in ORN number and cell proliferation, reduced extracellular matrix gene expression, and increased SASP contribute to olfactory impairment during aging.